EFFECT OF HIBISCUS FLOWERS (HIBISCUS ROSA-SINENSIS LINN.) ON EPIDIDYMIS, PROSTATE AND SEMINAL VESICLES - Carolin, Bunga Tiara; Salni, Salni; Nita, Sri (Biomedical Journal of Indonesia, 2019)
Hibiscus rosa-sinensis Linn. is one of the medicinal plants in Indonesia which is used as male contraception. Hibiscus flowers contain flavonoids which can reduce testosterone. The purpose of this study was to determine the effect of hibiscus flower extract on epididymal weight, cauda epididymal epithelial thickness, prostate weight and seminal vesicle of male rats. This research is an experimental study using a completely randomized design (CRD). The sample in this study used 25 male Sprague Dawley® strains aged 60-70 days with a body weight of 200-210 grams. The treatment dose is 200 mg / kg, 300 mg / kg, 400 mg / kg, 500 mg / kg for 30 days. The data is presented in tabular form and narrative to interpret the data. The results showed a decrease in epididymal weight in the treatment group compared to the control group (p = 0,000), there was also a thick shrinkage of the cauda epididymal epithelium (p = 0.021), a decrease in prostate weight and seminal vesicles between the treatment group versus the control group (p = 0.001). It can be concluded that there is an effect of hibiscus flower extract on the epididymis, prostate and seminal vesicles. The influence is likely due to the chemical content that is in hibiscus flowers that are antifertility.